Pelatihan Metode Pembelajaran dalam Jaringan di SD Muhammadiyah Sokonandi Yogyakarta (Daring GGZ) - Ingenida Hadning; Pinasti Utami; MT Ghozali; Sabtanti Harimurti; Amallia Puspitasari (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The Covid-19 pandemic is not just about health issues but also about social issues, one of which is the world of education. For that is necessary to use other alternative media in learning using the internet. However, some teachers are not proficient in using and operating online platform applications. Changing the way of learning requires teachers to know information technology. For this reason, training activities were held using the G Form, Google Meet, and Zoom applications to increase knowledge in using these platforms. This activity was carried out at SD Muhammadiyah Sokonandi, involving 18 teachers in classes 1-3. Methods for implementing this activity include planning, implementation, and evaluation. In the planning stage, the activity program is first drawn up. At the implementation stage, the training participants were given a pre-test, practical presentation, and mentoring accompanied by modules and ended with a post-test. In the final stage, data analysis was carried out using Microsoft Excel. The results of this activity indicate an increase in the understanding of class 1-3 teachers by 17,08%, and overall, 100% of teachers stated that this activity was beneficial. These results indicate that this training activity helps increase the knowledge of class 1-3 teachers who participated in the activity.